Applying Metacognitive Strategies in English for Missionary Course - Mahendra, Aloisius Wisnu (JET (Journal of English Teaching), 2019)
This study aimed at examining metacognitive strategies applied by eight missionaries during their learning in a specialized English course. As English has a significant influence to contribute to the spread of missionaries worldwide, a need of assisting the missionaries with sufficient use of English becomes a concern since they are required to use special expressions and skills to meet situational needs when they do their missions. This carries the notion of ESP on a contextual language learning specified for the missionaries as it provides opportunities for them to manage their learning. It encourages them to use metacognitive strategies during the course, focusing on planning for the learning strategy, monitoring the strategy use, and evaluating the whole learning. The current study was conducted in the Language Institute of Sanata Dharma University within the Center of English for Specific Purposes (CESP) division in 2018. Written reflections over the lessons were collected from the missionaries as the main data source. A document analysis, then, was employed to examine the data qualitatively. The findings showed how the missionaries applied the metacognitive strategies to assist their learning.